Ecosystem Services, Green Infrastructure and Spatial Planning (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
National governments hardly identify their ecological networks or make an effort to integrate them into their spatial policies and plans. Under this perspective, an important scientific and technical issue is to focus on preserving corridors for enabling species mobility and on achieving connectivity between natural protected areas. This Special Issue takes a step forward insofar as it aims at proposing a theoretical and methodological discussion on the definition and implementation of ecological networks that provide a wide range of ecosystem services.